Complement System: An Immunotherapy Target in Colorectal Cancer - Talaat, Iman M.; Elemam, Noha Mousaad; Saber-Ayad, Maha (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is the third most common malignant tumor and the second most fatal cancer worldwide. Several parts of the immune system contribute in fighting cancer including the innate complement system. The complement system is composed of several players, namely component molecules, regulators and receptors. In this review, we discuss the complement system activation in cancer specifically CRC and highlight the possible interactions between the complement system and the various TME components. Additionally, the role of the complement system in tumor immunity of CRC is reviewed. Hence, such work could provide a framework for researchers to further understand the role of the complement system in CRC and explore the potential therapies targeting complement activation in solid tumors such as CRC.